Conversion from Minimally Invasive Surgical Approaches to Open Surgery Among Patients with Endometrial Cancer in the SGO Clinical Outcomes Registry - Yousif, Abdelrahman; Ngo, Julie; Abdel-Gadir, Deena; Rocconi, Rodney P.; Timmins, Patrick; Lachance, Jason; Straughn, J. Michael; Dewdney, Summer; Lachance, Jenny; Mize, Benjamin; Chefetz, IIana (Annals of surgical oncology, 2025)
Background Endometrial cancer (EC) ranks as the most common gynecologic malignancy in the USA. While minimally invasive surgical (MIS) techniques have revolutionized EC management, conversion to laparotomy remains a concern due to the loss of laparoscopic benefits such as fewer surgical site infections and shorter hospital stays with reported rates varying widely. Factors influencing this conversion, including patient characteristics and tumor attributes, have not been fully understood. Our study aims to provide a framework for identifying patients at higher risk of conversion, thereby helping to inform surgical decision-making and patient counseling Addressing this gap, our study employs a national registry to analyze patient- and tumor-related factors associated with the transition from MIS to open surgery in EC. Patients and Methods We queried the SGO Clinical Outcomes Registry (COR) to identify all patients with EC who underwent surgical management. The COR indeed validated clinical data from 29 sites collected between 2014 and 2018. The primary outcome was to assess the conversion rate from MIS to open surgery. Descriptive statistics using means with standard deviations or frequency with percentages were used. Chi-squared analysis was used to examine the bivariate relationship between group status and the subjects’ demographic and clinical variables. Results A total of 3.4% (135/4028) of patients underwent conversion from MIS to open surgery. Demographic characteristics were balanced between the groups. Conversion was more prevalent in patients with obesity (29%) and morbid obesity (37%) than in patients who are underweight (2%), normal weight (16%), and overweight (16%). Similarly, conversion was more prevalent in patients with prior abdominal surgery (63% versus 52%; P = 0.001). Endometrioid (EC) predominated (59%) in the converted group, with higher-than-expected non-endometrioid rates (serous carcinoma 16%, clear cell carcinoma 4%, carcinosarcoma 5%, mixed histology 12%; all P < 0.01). Advanced International Federation of Gynecology and Obstetrics (FIGO) stages were more common in patients who converted to open surgery (stage II: 5%, stage III: 25%, stage IV: 9%; all P < 0.001). Type II (24%) and type III (5%) hysterectomies were more frequent in patients who converted to open ( P < 0.001). Logistic regression indicated body mass index (BMI), prior surgery, FIGO stage, histology, and hysterectomy type affected conversion ( P < 0.001), explaining 12.3% of the variance in the conversion outcome. Indications for conversion included uterine size, adhesions, and disease extent. Conclusions The adoption of MIS has become increasingly common standard of care for managing EC, attributed to enhanced perioperative outcomes. Factors associated with conversion such as uterine size, prior abdominal surgeries, surgical complexity, disease extent, and histologic types can affect the surgeon’s choice. Ultimately, a personalized surgical approach, tailored to individual patient attributes, remains pivotal for optimizing outcomes in EC management.